INDOKTRINASI PENDIDIKAN PADA MASA ORDE LAMA: MENANAMKAN NILAI PANCASILA DAN MANIPOL/USDEK - Yona Venelia Hutabarat; Daniel Parlindungan Sijabat, Rica Kharoma Andini (ADISAM PUBLISHER, 2023)
Indoctrination is a term that refers to the act of instilling certain doctrines or beliefs into the mind of a person or group. During the old order in Indonesia, indoctrination was carried out in all fields including education which was specifically used to instill values and beliefs in the country's philosophy, namely Pancasila. In emphasizing indoctrination, the education system specifically followed the decree issued by the president regarding the cultivation of Pancasila values. This can be seen with the birth of civic education subjects as a support, even the education system in the colonial era was also replaced in order to achieve a social life that fully loves the country.